2019
DOI: 10.1002/met.1838
|View full text |Cite
|
Sign up to set email alerts
|

Observed trends in daily extreme precipitation indices in Aguascalientes, Mexico

Abstract: Precipitation and its distribution greatly influence the evolution of ecosystems and the development of society. The objective was to analyse trends in extreme precipitation indices at 25 weather stations of Aguascalientes State. Eleven extreme precipitation indices were obtained. The time series of these indices were analysed with the non‐parametric Mann–Kendall test. The number of days above 50 mm, consecutive wet days, and extremely wet days did not have significant trends at any of the weather stations. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…A multiscale approach showed a significant increasing trend in the length of the MSD in the Pacific coast of Nicaragua, Honduras, and Guatemala, with increases estimated to be nearly 20 days per decade [232]. Drying may be one of the key observed climate change impacts for Mexico [233], with increasing trends in the number of consecutive dry days and decreasing trends in rainfall intensity for central Mexico. In contrast, increasing trends for rainfall were detected for north-western Mexico, although this may be attributed in most cases by the PDO [234].…”
Section: Observed Climate Changementioning
confidence: 99%
“…A multiscale approach showed a significant increasing trend in the length of the MSD in the Pacific coast of Nicaragua, Honduras, and Guatemala, with increases estimated to be nearly 20 days per decade [232]. Drying may be one of the key observed climate change impacts for Mexico [233], with increasing trends in the number of consecutive dry days and decreasing trends in rainfall intensity for central Mexico. In contrast, increasing trends for rainfall were detected for north-western Mexico, although this may be attributed in most cases by the PDO [234].…”
Section: Observed Climate Changementioning
confidence: 99%
“…Concerning precipitation, the results obtained in the present study were closely related to other investigations [72,74,76] in which precipitation patterns were found to be largely due to oscillations such as PDO and ENSO. Different regions in the center and north of the country present positive precipitation trends, but their statistical significance is very low, and studies such as [40,41] and [77] show that certain areas in northern Mexico have become more humid over the past decades. On the other hand, in states such as Chiapas and Veracruz, located in the country's south, research [36][37][38][39] has reported decreasing precipitation trends, with values of zero precipitation in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning precipitation, the results obtained in the present study were highly related to other investigations [67,69,71] in which precipitation patterns were found to be largely due to oscillations such as PDO and ENSO. Different regions in the center and north of the country present positive precipitation trends, but their statistical significance is very low, and studies such as [38,39] and [72] show that certain areas in northern Mexico have become more humid over the past decades. On the other hand, in states such as Chiapas and Veracruz, located in the country's south, research [34][35][36][37] has reported decreasing precipitation trends, with values of zero in some cases.…”
Section: Discussionmentioning
confidence: 99%